Les nouveaux outils de la tricherie scolaire au lycée - Christophe Michaut (Nantes Université, 2013)
With the arrival of mobile phones in classrooms and common use of the Internet in school activities, students have more opportunities to plagiarize documents or defraud during the tests on the table. Do the digital tools replace the traditional forms of cheating? What are the characteristics of cheaters? We will issue the hypothesis that these new tools are most frequently used by weak students and little engaged in school tasks. The survey of 1,909 students revealed that nearly 20% of them have used during their schooling, a mobile phone for cheating. However, cheating with using a cheat sheet or calculator is the most common. Multivariate analyses show that certain characteristics are common to the various tools, other more specific: General high school students will be, all other things being equal, more often resorted to a calculator. Students at low and investing little in their studies will more use a phone.